The medium, or the individual in the hypnotic state - Otten, Oscar Albert (My University, 1895)
Introduction: Most people today are free to think and speak as they please. Although superstition and mysticism have largely contracted the views and obstructed the vision of the thinking class, they are now nearly emancipated from those old dogmatic ideas. Still there is a small cloud lowering in the distant horizon. Science and reason have broadened the minds of all, and aided greatly in a partial removal of that ugly membrane, blinding the sight of the superstitions, so that clearer eyes create more accurately phenomena of all minds. From the nature of hypnotic phenomena people are apt to investigate it through the spears of superstition. Hypnotism being connected so closely with the affairs of life, and also bring so little understood, a great many instantly connect with the supernatural, closing their eyes to reason and common sense.
Citation: Otten, Oscar Albert. The medium, or the individual in the hypnotic state. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Superstition; Mysticism; Dogmatic ideas; Science; Theses; Manuscripts (documents)